PENGARUH TERAPI BERMAIN TERHADAP TINGKAT KECEMASAN ANAK USIA PRASEKOLAH AKIBAT HOSPITALISASI DI RSUD Dr. SOEKARDJO KOTA TASIKMALAYA - Sri Mulyanti; Tatang Kusmana (Jurnal BIMTAS: Jurnal Kebidanan Umtas, 2019)
Disease and hospitalization are often the first things children have to deal with. Children, especially during the early years, are particularly vulnerable to disease crises and hospitalization due to stress due to changes from normal health and environmental rutunisan, and children have a limited number of coping mechanisms to complete the stesor. Interventions that can be done, one of them with play activities or play therapy. Under conditions of illness or child hospitalization, this play activity is still carried out but must be in accordance with the condition of the child. With the games the child will be released from the tension and stress experienced, because by doing the game the child will be able to divert the pain on the game (distraksi) and relaxation through the pleasure of doing games. The purpose of this study was to determine the effect of play therapy on the anxiety level of children at preschool age due to hospitalization in RSU Dr.Soekardjo Kota Tasikmalaya. The writer in this research uses quantitative research method with quasy experiment research design. The population in this study were all preschool children (3-6 years) in the Floor V Floor of RSU Dr.Soekardjo Kota Tasikmalaya with 20 pre-school children sempel. From the result of wilcoxon test test with p value = 0,008, mean p value smaller than ? (0,05) which indicate there is change of child's anxiety response before given play therapy and after given play therapy. For hospitals to apply play therapy to reduce anxiety levels in children and this study can be useful for respondents, especially parents, that play therapy is very beneficial for children in reducing anxiety levels.